Comparative Analysis of the Effectiveness and Environmental Impact of Sawdust Biomass on Greenhouse Emissions for Power Plants Steam - Aulia Nafis Puspitarini; Budi Warsito; Fahrudin (Lembaga Teewan Journal Solutions, 2026)
Indonesia's dependence on fossil fuels, especially coal, causes greenhouse gas (GHG) emissions that have a significant impact on global climate change. As an energy transition solution, biomass is offered through co-firing technology at the energy industry's Steam Power Plants (PLTU). This study aims to analyze the sustainability of the use of biomass, especially sawdust, as an alternative fuel to replace some coal in the power generation sector. The Life CycleAssessment (LCA) approach is used to assess the environmental impact of the entire biomass life cycle, starting from the process of extracting raw materials, producing and drying sawdust, transportation to coal-fired power plants, to the combustion and residue disposal stages. The analysis was carried out using SimaPro software by considering various categories of environmental impacts, such as potential global warming (GWP), eutrophication, acidification, and depletion of natural resources. The results show that the use of sawdust biomass through co-firing has the potential to significantly reduce GHG emissions compared to the burning of pure coal, supports the Nationally DeterminedContribution (NDC) target, and contributes to the achievement of Sustainable Development Goals (SDG) 7 (Clean and Affordable Energy) and SDG 13 (Action on Climate Change).